Предмет: Алгебра, автор: michail228

пожалуйста на листочке

Приложения:

Ответы

Автор ответа: Dushzhanov987
0
 frac{x^2-3}{2} -6x=5         |*2
x^2-3-12x-10=0
x^2-12x-13=0
 left { {{x_1*x_2=-13} atop {x_1+x_2=12}} right.  {| {{x=13} atop {x=-1}} right.
Ответ: 13;-1

 frac{2x^2+x}{5} = frac{4x-2}{3}      |*15
3(2x^2+x)=5(4x-2)
6x^2+3x=20x-10
6x^2-17x+10=0
D=b^2-4ac
D=(-17)^2-4*6*10=289-240=49,D textgreater  0⇒2 р.д.к.
x_1= frac{-b+ sqrt{D} }{2a} = frac{17+ sqrt{49} }{12} = frac{17+7}{12} = frac{24}{12} =2
x_2= frac{-b- sqrt{D} }{2a} = frac{17- sqrt{49} }{12} = frac{17-7}{12} = frac{10}{12} = frac{5}{6}
Ответ:  frac{5}{6} ;2
Автор ответа: Dushzhanov987
0
Извините, я ошибку нашёл.
Автор ответа: michail228
0
помогите пожалуйста
Похожие вопросы